PELATIHAN PEMASARAN, PEMBERDAYAAN TOKO ONLINE, DAN PENGENALAN m-commerce PADA PRODUK UNGGULAN JAGUNG TORTILADI KECAMATAN TRUCUK KABUPATEN BOJONEGORO - Endriastuti, Annysa; Permatasari, Maurisia Putri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2018)
In todayâ€™s MEA (ASEAN economic community) era, the need to be more innovative in designing and marketing any products are necessary to those who run UMKM (Usaha Mikro Kecil danMenengah). However, one particular factor that fully hinders them is the holistic marketing processes besides capital, technology, and human resources. To further implement the solution, this paper concentrates on both UMKM MakmurAsri and TaniMakmur (in Tulungrejo, Trucuk, Bojonegoro), the manufacturer of tortilla snack, as the firms facing the mentioned trouble. Located far from the surrounding main roads, their location is by chance hard to reach. For the reason of distant constraint to customers, one better strategy is to apply the use of online shop andintroduce m-commerce model. Thus, by intensive training and mentoring, this iBM community service fills them in with all the details of the two combinations of marketing and English for business. It is with big hope that through applying this method can help the firms and their product be locally and internationally consumed and much more so.Â Key words: marketing, online store, m-commerce, tortilla corn.